Violent Conflicts and Challenges of Adjustment in Plateau State: Case Study of Jos North Local Government Area, Plateau State - Fagbite, Bamidele Emmanuel; Faleti, Stephen Ademola; Yusuf, Olanrewaju (African Journal of Stability and Development (AJSD), 2018)
Nigeria is confronted with numerous violent conflicts that have inflicted monumental damages on the economy and peaceful co-existence amongst groups. These conflicts assume ethnic and religious forms leading to depletion of human resources/displacement, weakened state apparatus, and increased threats of secession. A fact is that states with multiple ethnicity and religions are prone to violent conflicts. This becomes more pronounced with underlying indigenship/ settlership debate. Conflicts in Plateau State are often deeply ethnic-based; religious factor has also remained a shadow trigger. The frequency of conflicts had led to trends of relocation, adjustment and even protracted conflicts in the deeply polarised state. This paper looks at structural adjustment as essential in the discussion of the pattern post conflict residency, settlement and human endeavour in Jos North LGA of Plateau State. It agrees with submissions of Richard Lazarus (1961) on theories of adjustment and personality; adopting a mixed design approach, while some KIIs were conducted as primary sources of data collection along secondary sources which were qualitatively analysed. Strengthening security and peace architecture including promotion of human security in prevention, rather than response to violence, will help in the healing process of the fragmented communities and people